In Situ Subcellular Detachment of Cells Using a Cell‐Friendly Photoresist and Spatially Modulated Light. Issue 14 (17th May 2019) - Park, Jeehun; Kim, Taeyup; Choi, Jong Chul; Doh, Junsang
Abstract: Dynamic adhesion and detachment of subcellular regions occur during cell migration, thus a technique allowing precise control of subcellular detachment of cells will be useful for cell migration study. Previous methods for cell detachment were developed either for harvesting cells or cell sheets attached on surfaces with low resolution patterning capability, or for detaching subcellular regions located on predefined electrodes. In this paper, a method that allows in situ subcellular detachment of cells with ≈1.5 µm critical feature size while observing cells under a fluorescence microscope is introduced using a cell‐friendly photoresist and spatially modulated light. Using this method, a single cell, regions in cell sheets, and a single focal adhesion complex within a cell are successfully detached. Furthermore, different subcellular regions of migrating cells are detached and changes in cell polarity and migration direction are quantitatively analyzed. This method will be useful for many applications in cell detachment, in particular when subcellular resolution is required. Abstract : A method that allows in situ high‐resolution subcellular region detachment is developed. Using this method, a single cell, cells in cell sheets, and a single focal adhesion complex within a cell are successfully detached. In addition, different subcellular regions of migrating cells are detached and influences of subcellular detachment in cell polarity and migration are quantitatively analyzed.